2023
DOI: 10.1093/ejendo/lvad123
|View full text |Cite
|
Sign up to set email alerts
|

Anorexia nervosa and adrenal hormones: a systematic review and meta-analysis

Subhanudh Thavaraputta,
Patompong Ungprasert,
Selma F Witchel
et al.

Abstract: Objective Anorexia nervosa is a primary psychiatric disorder characterized by self-induced negative energy balance. A number of hormonal responses and adaptations occur in response to starvation and low body weight including changes in adrenocortical hormones. Our objective was to systematically review adrenocortical hormone levels in anorexia nervosa. Design/Methods We searched MEDLINE and EMBASE for studies that reported at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…In another study, where 49 obese patients (body mass index (BMI) 32.2-67.1 kg/m 2 ; 25 women and 24 men) underwent one-day fasting, it was indicated that the cortisol levels were increased [126]. While these results may be different in a daily fasting episode with no calorie intake for less than 24 h, they match the conclusion that no calorie intake, similar to starvation, increases cortisol levels [53,54]. There is an inverse relation between a low BMI, fat mass, and glucose and insulin concentrations and higher levels of cortisol, which is consistent with the finding that the release of cortisol is enhanced as an adaptation response to starvation threats [16].…”
Section: Release Of Cortisol From Adrenal Glands During Fasting and S...mentioning
confidence: 80%
See 1 more Smart Citation
“…In another study, where 49 obese patients (body mass index (BMI) 32.2-67.1 kg/m 2 ; 25 women and 24 men) underwent one-day fasting, it was indicated that the cortisol levels were increased [126]. While these results may be different in a daily fasting episode with no calorie intake for less than 24 h, they match the conclusion that no calorie intake, similar to starvation, increases cortisol levels [53,54]. There is an inverse relation between a low BMI, fat mass, and glucose and insulin concentrations and higher levels of cortisol, which is consistent with the finding that the release of cortisol is enhanced as an adaptation response to starvation threats [16].…”
Section: Release Of Cortisol From Adrenal Glands During Fasting and S...mentioning
confidence: 80%
“…The nature of the eligible studies was one book chapter, forty-two review studies, and forty-five clinical studies, which are indicated in Table S1 as well. ↑Gluconeogenesis [46] ↓Peripheral tissue glucose uptake and utilization [47] ↑Glycogenolysis [48] ↓Leptin leading to ↑Cortisol [49] ↓Cortisol [50] Starvation ↑Cortisol [20,36,[51][52][53][54][55][56][57][58][59][60][61] ↑Gluconeogenesis [62] ↑Amino acids [63] *…”
Section: Characteristics Of Included Workmentioning
confidence: 99%